Hip Arthroscopy Procedural Volume Is Low Among Graduating Orthopaedic Surgery Residents - Suleiman Y. Sudah, M.D; Christopher R. Michel, M.D; Matthew H. Nasra, B.S; Robert D. Faccone, B.S; David S. Constantinescu, M.D; Mariano E. Menendez, M.D; Ryan J. Plyler, M.D (Elsevier, 2022)
Purpose: The purpose of this study was to evaluate case volume and variability of hip arthroscopy exposure among graduating orthopaedic residents. Methods: The Accreditation Council for Graduate Medical Education (ACGME) surgical case log data from 2016 to 2020 for graduating United States orthopaedic surgery residents were assessed. Arthroscopy procedures of the pelvis/hip were identified. The average number of cases performed per resident was compared from 2016 to 2020 to determine the percent change in case volume. The 10th, 30th, 50th, and 90th percentiles of case volumes from 2016 to 2020 were presented to demonstrate case volume variability. Results: There was no change in the number of hip arthroscopy procedures between 2016 and 2020 [average: 8.4 ± 10 (range: 0 to 87) vs. 9.8 ± 12 (range: 0 to 101)] (P = .995). There was a wide variability in case volume among residents. The 90th percentile of residents performed 24 cases in 2020, compared to 2 cases in the 30th percentile and 0 cases amongst the 10th percentile of residents. Conclusions: Despite the growing popularity of hip arthroscopy, resident exposure to this highly technical procedure remains limited, with about one-third of residents performing 2 or less cases by graduation. Clinical Relevance: Understanding case volume and variability is important for orthopaedic surgery programs to ensure that graduating residents are gaining adequate exposure.